An Analysis of Factors Influencing Customer Satisfaction in Sharia Insurance: A Systematic Literature Review - Dina Rusda; Luqman Hakim Handoko (UIN Sunan Kalijaga Yogyakarta, 2025)
Research: This investigation seeks to survey the existing body of literature concerning customer satisfaction within the Sharia insurance sector, to delineate the principal factors that shape customer contentment, and to construct a conceptual framework predicated upon these pivotal determinants. Design/methodology/approach: The study employs a Systematic Literature Review (SLR) methodology, integrated with a descriptive qualitative approach, following the PRISMA protocol. Data were procured from Google Scholar, utilizing the Publish or Perish software, with the search terms “kepuasan nasabah asuransi syariah” and “Sharia Insurance Customer Satisfaction.” An initial corpus of 41 articles was rigorously screened, culminating in a final selection of 11 seminal papers. A thorough content analysis was subsequently performed to identify, categorize, and interpret the collated research findings. Research Findings: The review revealed a fluctuation in publication output between 2020 and 2025, peaking in 2023 with the issuance of five articles. The analysis identified five predominant factors that materially affect customer satisfaction: service quality, premium rates, brand image, Sharia-compliant marketing, and product quality. Theoretical Contribution/Originality: This research furnishes a systematic overview specifically centered on customer satisfaction in Sharia insurance, thereby addressing a significant lacuna in the literature that has hitherto remained underexplored in a comprehensive manner using the SLR method. Research limitation and implication: The scope of this inquiry is confined to 11 articles indexed in Google Scholar published between 2020 and 2025. Notwithstanding this limitation, the findings provide a foundational reference for subsequent academic research and offer salient practical implications for Sharia insurance enterprises aiming to enhance customer satisfaction through the fortification of service quality, premium structures, brand reputation, ethical marketing strategies, and product offerings.